Randbemerkungen zur Diskussion über das System der Geographie - Markos, Georg (ERDKUNDE, 1963)
The development of the field of geography since the beginnig of the last century differed greatly between the physical and the socio-economic branches. On the physical side, owing to the increase in knowledge, some branches have become separated from geography and have acquired independent status. The branches which study human and social problems in relation to space, e.g. cultural geography, settlement geography, economic geography, commercial geography, have investigated merely parts of this field; in doing this physical geography rather than the social studies has tended to be the basis and a clear hierarchy of concepts and disciplines is still lacking. All social processes take place in materially filled space. Production, trade, etc., are however not only dependent on the physical factors but also on the human-social circumstances, the stage of technology, the forces of production and the respective social system. What is valid for economic geography in particular is however also valid for all other branches which are concerned with problems of space and the following three closely related factors determine the economic conditions of any society: 1) Physical nature 2) the relationship between Man and Nature (forces of production, infra-structure, technology) 3) the relationship of social groups to each other (states, professions or occupations, classes). Economic regions are in addition also determined by non-economic factors. An economic region is a complex entity with actions and counteractions originating within all the time. From this complex being one may abstract items only in one's mind to investigate individual aspects but must never lose sight of the whole. The economic region is a concrete reality not merely a concept to be formed in one's mind but an entity to be discovered by research. This discovery of economic regions by the geographer re quires knowledge of the social studies, political economy and technology just as the various branches of physical geography require the natural sciences as their bases. It is a known fact that the field of geography is split into two or more correctly three groups of disciplines whose object is to investigate inanimate nature, animate nature and social phenomena as occurring within concrete, given space. Geography cannot therefore be fitted into the traditional system of knowledge. It is a specific group of branches of learning of which some belong to the natural sciences, others to the social studies. The unity of geography no longer exists according to its object of investigation but it can be regained at a higher level on the basis of the peculiar point of view and geographical method, i.e. the analysis of concrete phenomena, processes and their inter relationships within the objectively existing space. The discovery of these interrelationships and laws may then be utilised in practical life in the interest of progress.